Research on Wearable ECG Device for Health IoT Applications - Mao, Xiaojun (fi=Turun yliopisto|en=University of Turku|, 2017)
Electrocardiogram (ECG) monitoring has been widely applied in diagnosis and prevention of heart related diseases with the development of science and the deep research on cardiovascular health. However, it is difficult for the existing ECG detection instrument to implement household monitoring for its large volume and high price. This thesis designs and implements a wearable ECG monitoring device for the Internet of things (IoT) applications, in order to overcome the disadvantages of the existing ECG monitoring technology in the long-term ECG monitoring. The device is wearable and can realize real-time ECG acquisition to make up for the defects of the professional medical equipment and the existing intelligent equipment. Principle for the ECG device design follows the current professional ECG instrument instead of the light reflection detection which is adopted by most of the intelligent equipment. It can be applied as home healthcare device which can provide medical value. The system is divided into ECG acquisition equipment and data control center. The design of ECG acquisition equipment is based on the intelligent ECG chip, and transmission protocol is designed in detail. Besides, the problem of signal interference and data integrity is analyzed and solved. The shell of the device is also designed with the three dimensional (3D) print technology and suitable material to realize a comfortable wear. The software consists of ECG data processing, system monitoring and management, and user interface design. Finally, the reliability and feasibility of the design is verified through testing the performance of the device in different situations. The research work of this paper provides reference value for the intelligent health system which is widely adopted in the IoT.